Game Edu IT: Combining Technology Literacy with an Interactive Approach - Fortilla, Zeny Arsya; Al-Ghazali, Taufiq Akbar (Gameology and Multimedia Expert, 2025)
This study aims to integrate technology literacy into the learning process through an interactive approach packaged as an educational game application developed using Scratch. The game is designed with a question-and-answer system to stimulate players' awareness of their abilities and enhance their curiosity about technology. Players will earn points as rewards for successfully answering questions posed by the game's characters, offering both engaging entertainment and educational value. Through "Game Edu IT," this application is expected to provide an enjoyable learning experience while broadening users' knowledge of information technology (IT) in a playful manner. The game is designed to increase learning interest and improve users' understanding of technology literacy, establishing it as an effective educational tool.